1996
DOI: 10.1145/234215.234473
|View full text |Cite
|
Sign up to set email alerts
|

Toward real microkernels

Abstract: The inefficient^ inflexible first generation inspired development of the vastly improved second generation^ which may yet support a variety of operating systems.HE microkernel story is full of good ideas and blind alleys. The story began with enthusiasm about the promised dramatic increase in flexibility, safety, and modularity. But over the years, enthusiasm changed to disappointment, because the first-generation microkernels were inefficient and inflexible. • Today, we observe radically new approaches to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(54 citation statements)
references
References 14 publications
0
54
0
Order By: Relevance
“…This first generation of microkernels such as Mach [41] or IBM's Workplace OS [21] suffered from a poor performance. When Jochen Liedtke analyzed these systems [35], he pinned the problem down to a feature-overloaded mechanism for inter-process communication (IPC). Together with a light-weight, flexible IPC mechanism [33], he proposed the minimality of hardware abstractions [34] in the kernel and suggested that servers implement the traditional services of operating systems.…”
Section: Microkernel Designmentioning
confidence: 99%
“…This first generation of microkernels such as Mach [41] or IBM's Workplace OS [21] suffered from a poor performance. When Jochen Liedtke analyzed these systems [35], he pinned the problem down to a feature-overloaded mechanism for inter-process communication (IPC). Together with a light-weight, flexible IPC mechanism [33], he proposed the minimality of hardware abstractions [34] in the kernel and suggested that servers implement the traditional services of operating systems.…”
Section: Microkernel Designmentioning
confidence: 99%
“…The high-level PERSEUS architecture is illustrated in Figure 2. The PERSEUS security kernel is based on the efficient L4 microkernel [25,18] that provides (i) a hardware abstraction, (ii) elementary mechanisms, and (iii) flexible policies that are required to control and protect critical system services, device drivers and resource managers as separated user-space processes (a socalled multi-server system). This prevents that errors of one component can affect others, ensures that only authorized processes can access the hardware and guarantees that only the microkernel itself is executed in the supervisor mode of the CPU.…”
Section: Perseusmentioning
confidence: 99%
“…Microkernel operating systems (OSes) [1], [2] architecture involves the implementation of near-minimum OS functions as a kernel; these include scheduling, memory management, and interprocess communication (IPC) functions. Other OS functions are implemented as processes (OS servers).…”
Section: Introductionmentioning
confidence: 99%